0
$\begingroup$

Termials = a,b,c.
non-Termials = A,S.
Production Rules:
(1) S → aS
(2) S → bA
(3) A → bA
(4) A → cA
(5) A → c
(6) S → a
How do you write the following in normal form, I understand that it is currently not a context free grammar language of normal form , so I want to modify to be.

$\endgroup$
  • $\begingroup$ How do you convert different values for one non - terminal of production rules to CNF? $\endgroup$ – Sue Jan 23 '19 at 10:51
  • $\begingroup$ By CNF in your comment you mean Chomsky Normal Form? In the question you do not specifiy. There are also Greibach Normal Form and other normal forms for CFG. For CNF you can easily find conversion algorithms. $\endgroup$ – Peter Leupold Jan 23 '19 at 12:00
  • $\begingroup$ @Sue A good start is to actually understand the grammar you're given. Can you describe what the words it creates are? $\endgroup$ – Nick Peterson Jan 23 '19 at 18:52

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Browse other questions tagged or ask your own question.